2018
DOI: 10.1111/jvs.12670
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation patterns along agricultural land abandonment in the Balkans

Abstract: Question What are the woody vegetation encroachment patterns after agricultural land abandonment? Focusing on two parameters, woody plant species richness and vertical vegetation heterogeneity (number of different vegetation strata and their relative cover) we investigated: (a) the effect of forest encroachment following land abandonment; (b) the comparative importance of forest encroachment vis‐a‐vis topographic and climatic parameters, and finally; (c) the ecological importance of eight land‐cover types enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 77 publications
(105 reference statements)
0
6
0
1
Order By: Relevance
“…According to the model, the shrubland (25.2%) and rock (32.7%) classes will be major contributors to woodland expansion. This dynamic corresponds to the vegetation's natural development and will obviously be influenced by any unpredictable forest fires (Lasanta-Martínez et al 2005;Zakkak et al 2018;Heydari et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…According to the model, the shrubland (25.2%) and rock (32.7%) classes will be major contributors to woodland expansion. This dynamic corresponds to the vegetation's natural development and will obviously be influenced by any unpredictable forest fires (Lasanta-Martínez et al 2005;Zakkak et al 2018;Heydari et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies found that increasing woody species cover (Řehounková et al ; Zakkak et al ) changed specific habitat conditions and gradually decreased the habitat heterogeneity of post‐mining sites. This may lead to the complete disappearance of threatened species specialized for at least partly open successional stages (Ursic et al ).…”
Section: Discussionmentioning
confidence: 99%
“…In southeast Europe, such as in Bulgaria and Croatia, plant species diversity is greatly affected by elevation and temperature. In areas with low elevation and cold temperatures, species are more abundant [ 139 ]. However, the richness of bird species declines after farmland abandonment, highlighting the importance of the management and maintenance of traditional rural landscapes in this area.…”
Section: Resultsmentioning
confidence: 99%